Pendampingan Ibu Hamil dalam Peningkatan Parenting Self Effication melalui Peer Group Telling Story di Puskesmas Bangetayu: Assistance for Pregnant Women in Increasing Parenting Self Efficacy through Peer Group Telling Story at the Bangetayu Community Health Center - Meiranny, Arum; Arisanti, Atika Zahria (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Mothers who accept their pregnancy positively can prepare themselves and carry out their role well. Achieving her role as a mother through psychological changes during pregnancy is a woman's task that must be achieved because failure can have a negative impact. The number of pregnant women at the Bangetayu Community Health Center is 30 people. Nearly 60% of pregnant women have poor parenting self-efficacy. Parenting self-efficacy is very necessary during pregnancy and the postpartum period. The solution to this problem aims to increase parenting self-efficacy and optimize the motivation of pregnant women to increase knowledge with a discussion approach among pregnant women through telling story group discussions. The implementation of activities involving the application of science and technology was carried out twice, namely on October 8, 2023, and November 5, 2023, targeting pregnant women at the Bangetayu Community Health Center, Semarang City. Science and technology transfer begins with a pre-test and ends with a post-test. Education is delivered using an easy-to-understand method: providing material and forming groups to tell stories. Parenting self-efficacy of pregnant women from the pre-test and post-test results increased by 8.85%. The most important thing about this activity is that mothers will teach other pregnant women.